Scandinavian clinical practice guideline on fluid and drug therapy in adults with acute respiratory distress syndrome. Issue 6 (14th March 2016) - Claesson, J.; Freundlich, M.; Gunnarsson, I.; Laake, J. H.; Møller, M. H.; Vandvik, P. O.; Varpula, T.; Aasmundstad, T. A.
Abstract : Background: The objective of the Scandinavian Society of Anaesthesiology and Intensive Care Medicine (SSAI) task force on fluid and drug therapy in adults with acute respiratory distress syndrome (ARDS) was to provide clinically relevant, evidence‐based treatment recommendations according to standards for trustworthy guidelines. Methods: The guideline was developed according to standards for trustworthy guidelines, including a systematic review of the literature and use of the GRADE methodology for assessment of the quality of evidence and for moving from evidence to recommendations. Results: A total of seven ARDS interventions were assessed. We suggest fluid restriction in patients with ARDS (weak recommendation, moderate quality evidence). Also, we suggest early use of neuromuscular blocking agents (NMBAs) in patients with severe ARDS (weak recommendation, moderate quality evidence). We recommend against the routine use of other drugs, including corticosteroids, beta2 agonists, statins, and inhaled nitric oxide (iNO) or prostanoids in adults with ARDS (strong recommendations: low‐ to high‐quality evidence). These recommendations do not preclude the use of any drug or combination of drugs targeting underlying or co‐existing disorders. Conclusion: This guideline emphasizes the paucity of evidence of benefit – and potential for harm – of common interventions in adults with ARDS and highlights the need for prudence when considering use of non‐licensed interventions in this patient population.